Intervención del médico de familia en el diagnóstico del cáncer - Simó Cruzet, E. (Aten Primaria, 2000)
OBJECTIVE: To find the intervention of family doctors (FD) in diagnosing tumour pathology. DESIGN: Retrospective descriptive study. SETTING: Urban primary care centre. PATIENTS: Patients over 14 diagnosed with cancer. MEASUREMENTS: Selection of patients from the computerised records between November 1989 and March 1997. Review of clinical histories, analysing: 1. Personal details, 2. Type of cancer, 3. Intervention of the FD in the diagnosis, 4. Symptom of initial consultation, 5. Further tests requested by FD, 6. Interval between consultation and diagnosis, 7. Survival and 8. interval between diagnosis and death. FD intervention in diagnosis was evaluated: 1. Impossible intervention, 2. No intervention, with suspect signs not valued (SSNV) or with suspect signs valued (SSV), 3. Diagnostic intervention, incomplete (Iin) or complete (Ico). RESULTS: 438 tumours were detected: in 256 men (59%) and 171 women (41%). The most common kind in men was lung cancer (46 cases, 17%), and in women breast cancer (59 cases, 34%). In 233 cases (53%) the intervention of the FD was impossible. In 29 cases (6.5%) the FD’s intervention was nil (15 cases with SSNV, 14 cases with SSV). Of the 174 cases (39.6%) in which the FD intervened, full diagnosis was made in 40% (69 cases). The mean of the interval between the first consultation and the diagnosis was significantly less when FD intervention existed, at 1.95 months (CI, 0.63-1.06) in Ico and 2.9 months (CI, 0.51-2.19) in Iin, than when there was no intervention, with delays of 5.58 months (CI, 1.46-3.53) with SSNV and 10.5 months (CI, 8.45-12.54) with SSV (p = 0.000). CONCLUSIONS: The family doctor can play an important part in cancer diagnosis. His/her active intervention can reduce the interval between consultation and diagnosis.